Predictors of eligibility for reimbursement of antiviral treatment in HBe-Ag negative chronic hepatitis B patients with high ALT levels: Predictors of eligibility for reimbursement of antiviral treatment - Engin, İsmail; Duman, Ali Erkan; Ataoğlu, Hayriye Esra; Örmeci, Aslı Çifçibaşı; Poturoğlu, Şule (Journal of Surgery and Medicine, 2022)
Background/Aim: A liver biopsy is required for the reimbursement of antiviral therapy in Hepatitis B e-antigen (HBe-Ag) negative chronic hepatitis B patients. Liver biopsy is an invasive procedure with potential complications, such as bleeding, pain, pneumothorax, and even death. The study aimed to evaluate simple and non-invasive parameters that may help predict histological criteria that would be eligible for antiviral treatment reimbursement. Methods: HBeAg-negative chronic hepatitis B patients with alanine transaminase (ALT) levels > upper normal limit (40 IU/L) and HBV DNA viral load > 2000 IU/ml who underwent liver biopsy were enrolled in this retrospective cohort study. ALT, aspartate aminotransferase (AST), alpha-fetoprotein (AFP) values, hepatitis B virus (HBV) DNA levels, platelet count, and hepato-steatosis grade based on ultrasonography were used to predict the eligibility for antiviral therapy reimbursement. Eligibility for reimbursement of antiviral treatment regarding histological criteria defined by National Social Security Institution is based on the hepatitis activity index (HAI) score ≥ 6 and/or fibrosis score ≥ 2 according to Ishak’s scoring system. Results: One hundred and fifteen patients were included in the study; 79 patients (68.7%) were male. The mean age of patients was 46.51 (11.39). Sixty-two patients (53.9%) had a fibrosis score ≥ 2, and 80 (69.6%) patients had an HAI score ≥ 6. Ninety-two (80%) of the patients fulfilled histological criteria for antiviral treatment reimbursement. Multivariate analysis revealed that age and platelet count were independent predictors of eligibility for antiviral treatment reimbursement. The platelet count cut-off point was 198 x 109 /L for predicting eligibility for antiviral treatment reimbursement. Conclusion: Most patients (92/115, 80%) with high ALT and DNA viral load were eligible for antiviral treatment reimbursement. Platelet count and age may be used as simple non-invasive parameters for predicting the eligibility for antiviral treatment reimbursement in terms of histological findings.